Beethoven Centennial Memorial sponsored by the Tuesday Musical Club ... Saturday, March 26h, 1927, at 8:30 o'clock, Municipal Auditorium, San Antonio, Texas. (San Antonio, TX; United States; Lodovic Ptg., 2020)
Program of an event commemorating the 100th anniversary of Beethoven's death. It that included a film with "scenes from the life of Beethoven;" an address by an actor portraying Beethoven; performances of the Gellert Lieder by the Beethoven Maennerchor; the Fifth Symphony performances by an ensemble of 26 female pianists; the aria "Abscheulicher, wo eilst du hin?" from Fidelio; the "Appassionata" Sonata; the Egmont Overture; and the Minuet in G. The audience was asked to stand during the concluding work, the funeral march from the Sonata in A-flat Major, Opus 26.